1997
DOI: 10.1093/jn/127.5.668
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenoids Suppress the Growth of Murine B16 Melanomas In Vitro and In Vivo

Abstract: Sundry mevalonate-derived constituents (isoprenoids) of fruits, vegetables and cereal grains suppress the growth of tumors. This study estimated the concentrations of structurally diverse isoprenoids required to inhibit the increase in a population of murine B16(F10) melanoma cells during a 48-h incubation by 50% (IC50 value). The IC50 values for d-limonene and perillyl alcohol, the monoterpenes in Phase I trials, were 450 and 250 micromol/L, respectively; related cyclic monoterpenes (perillaldehyde, carvacrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
162
2
15

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 256 publications
(187 citation statements)
references
References 25 publications
8
162
2
15
Order By: Relevance
“…The potency of tocotrienol isoforms in anticancer activity display a relationship corresponding to ␦-tocotrienol Ͼ ␥-tocotrienol Ͼ T3. 34 Although ␦-tocotrienol and ␥-tocotrienol have strong anticancer potential, these isoforms are highly toxic toward normal cells. 35 Modification of the isoformdependent anticancer properties by blocking antioxidant activity may also cause high toxicity toward normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The potency of tocotrienol isoforms in anticancer activity display a relationship corresponding to ␦-tocotrienol Ͼ ␥-tocotrienol Ͼ T3. 34 Although ␦-tocotrienol and ␥-tocotrienol have strong anticancer potential, these isoforms are highly toxic toward normal cells. 35 Modification of the isoformdependent anticancer properties by blocking antioxidant activity may also cause high toxicity toward normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion b-Ionone, a pure isoprenoid, has been shown to possess potent antiproliferative activity 9,13,17 and to induce apoptosis 10,12 in cancer cells. Liu's study 9 reported that b-ionone at doses of 25-200 lmol/l inhibited cell proliferation and DNA synthesis in human mammary cancer MCF-7 cells in a dose-dependent manner.…”
Section: Expression Of Apoptosis Bcl-2 and Bax In Mammary Cancer Tismentioning
confidence: 99%
“…In addition, b-ionone also affected the progression of metastasis in SGC-7901 cells 11 and B16 cells. 12,17 In this study, female Sparague-Dawley rats were fed 3 levels of 9.0 (low), 18.0 (medium) and 36.0 mmol/kg (high) of b-ionone in the AIN-76A diet, starting 2 weeks before DMBA administration and continuing for the 24 weeks until the end of the experiment. The positive control group, given the DMBA, developed mammary tumors with 82.1% tumor incidence during the 24-week study, and no tumors were detected in the negative control group without DMBA.…”
Section: Expression Of Apoptosis Bcl-2 and Bax In Mammary Cancer Tismentioning
confidence: 99%
See 2 more Smart Citations